Ethical Provision of Online Learning in South African High Schools - Chipangura, Baldreck (Journal of Information System and Informatics, 2024)
Drawing from Kantianism, utilitarianism, information systems ethical models, and South Africa Department of Education policies, this study investigated how high schools can ethically provide online learning. The study was prompted by two unethical concerns highlighted in the literature: firstly, the potential discrimination to online learning against learners who do not have access to information technology resources, and secondly, the cyber risks faced by learners from prolonged exposure to Internet connected devices. To gather data for the study, interviews were conducted with 15 schoolteachers, who were conveniently sampled from five schools in Centurion, Pretoria city, South Africa. The data was thematically analysed, and the results of the study found constructs that inform ethical provision of online learning, which are: equal access to online learning, teacher competence, teacher empathy, and cyber security of learners. The findings of this study inform the policy on providing ethical online learning in South Africa and any other country.